Effects of Strategies Marketing of Collective Buying about Impulsive Behavior - Dias, Suzi Elen Ferreira (2014)
Brazil has the second largest e-commerce market in the world. One model used in this sector is "collective buying", a feature of which is impulse sales. Consumer behavior can be influenced by several factors, two of which are addressed in this article: the individual impulsivity of consumers and strategies of mix marketing. Impulsive buying is characterized by an unplanned purchase, i.e. the need to acquire the product arises just before the purchase. Consumers respond differently to mixed strategies depending on their degree of impulsivity. Thus, this article aims to analyze the efficacy of different marketing mix strategies for impulsive and non-impulsive consumer purchasing behavior. 137 participants were given a questionnaire containing the Buying Impulsiveness scale from Rook and Fisher (1995), and statements about the marketing strategies used by collective buying sites. Through a regression analysis, three strategies were found to relate more to impulsivity: search for products from well-known brands, search for deals with big discounts and confidence in receiving the product. For e-commerce and researchers, this study elucidates which strategies, from the consumer's perspective, effectively persuade purchasing behavior.